Purification, characterization and substrate specificity of thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) - Gote, M. M.; Khan, Mohammad Islam; Gokhale, D. V.; Bastawade, Kulbhushan B.; Khire, Jayant Malhar (Process Biochemistry, 2006)
An extracellular thermostable alpha-galactosidase from Bacillus stearothermophilus (NCIM-5146) has been purified to homogeneity by chromatographic step, using Phenyl Sepharose CL-4B column. The specific activity of the enzyme was increased approximately 389-fold, from 1.03 U/mg protein to 400 U/mg protein. The molecular mass of the purified enzyme as determined by SDS-PAGE and gel filtration was 79.9 and 165.9 kDa, respectively, suggesting dimeric nature. The purified alpha-galactosidase is a non-glycosylated protein with a pI of 4.9. The pH and temperature optima for the purified enzyme are 6.5-7.0 and 65 degrees C, respectively. The alpha-galactosidase is stable over a broad pH range (3-9) and its half-life of inactivation (t(1/2)) at 70 degrees C is 30 min. The partial N-terminal sequence of alpha-galactosidase showed remarkable homology (80% similarity) with earlier reported alpha-galactosidase from B. stearothermophilus NUB 3621. The secondary structure of the enzyme determined by circular dichroism (CD) spectroscopy exhibited alpha/beta class of protein and showed temperature induced conformational forms below and above the transition temperature. The purified enzyme showed biphasic Arrhenius plot with break point at 55 degrees C for pNPG and 50 degrees C for melibiose, raffinose and stachyose. The enzyme hydrolyzes alpha-1-3, alpha-1-4, and alpha-1-6 galactosidic linkages and not the beta-galactosidic linkages. Synthetic substrates pNPG and oNPG had lower K-m and higher K-cat as compare to natural substrates, melibiose, raffinose, and stachyose. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha-galactosidase; Bacillus stearothermophilus (NCIM-5146); Purification; Secondary structure; thermostable enzyme

Active site directed chemical modification of alpha-galactosidase from bacillus stearothermophilus (NCIM 5146): involvement of lysine, tryptophan and carboxylate residues in catalytic site - Gote, M. M.; Khan, Mohammad Islam; Khire, Jayant Malhar (Enzyme and Microbial Technology, 2007)
The catalytic amino acid residues of the extracellular a-galactosidase (alpha-D-galactoside galactohydrolase; EC 3.2.1.22) from Bacillus stearothermophilus NCIM 5146 were investigated by pH dependence and chemical modification studies. These results suggested that carboxylate and a lysine residue take part in catalysis and only lysine residues were essential for substrate binding. Carbodiimide mediated chemical modification of the enzyme also supported that a carboxylate residue located in the active site act as a nucleophile base in substrate cleavage. Acylation and reductive methylation of lysine residues by acetic, citraconic anhydride and sodium borohydride suggested that four protonated lysine residues carrying positive charge on its epsilon-amino group provides the positive charge density for binding of the substrate. Additionally four tryptophan residues also found near to the active site and in a moderately hydrophobic environment. Kinetic and thermal inactivation study of modified enzyme indicated that these tryptophan residues might have a role in the catalytic site as well as in the thermal stabilization of active site conformation at higher temperature. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Active site; alpha-galactosidase; Bacillus stearothermophilus; carboxylate; Chemical modification; lysine; Tryptophan